The Effect of “Buy Now, Pay Later” On Personal Financial Distress Through Impulsive Buying and Financial Management Behavior as Chain Mediation Among Generation Z in DKI Jakarta - Nurhana Kholifah; Osly Usman (Eduvest - Journal of Universal Studies, 2026)
The expansion of Buy Now, Pay Later (BNPL) services among Generation Z raises serious concerns about personal financial health. This study examines the effect of BNPL usage on personal financial distress, with impulsive buying and financial management behavior as chain mediators, among 264 valid Generation Z respondents aged 17 to 27 years who live or work in DKI Jakarta. Based on Behavioral Finance Theory as the grand theory and supported by the Theory of Planned Behavior, Mental Accounting Theory, Social Cognitive Theory, Impulsive Buying Theory, and Cognitive Dissonance Theory, a multiple chain mediation model with seven hypotheses was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4 with 5,000 bootstrap subsamples. The results show that BNPL usage has a significant positive effect on personal financial distress (β = 0.285; p = 0.002) and a very strong effect on impulsive buying (β = 0.817; p < 0.001). Impulsive buying is shown to mediate the effect of BNPL usage on personal financial distress (β = 0.372; p < 0.001), and this indirect path exceeds its direct effect, resulting in partial mediation. In contrast, all paths involving financial management behavior were not statistically significant, a finding that was transparently reported and partly attributed to limitations in measurement quality and the low statistical power of the construct. Practically, these findings direct consumer protection and financial literacy efforts for young users toward targeting impulsive moments during transactions rather than focusing solely on financial knowledge.